Economic Inequality, Social Determinants of Health, and the Right to Social Security - Joo-Young Lee (Harvard FXB Center for Health and Human Rights, 2023)
This paper discusses economic inequality as a key social determinant of health. It highlights the potentially transformative role of social protection systems in addressing economic inequality and health inequalities. How to finance social protection and how to distribute benefits among people are key questions in the pursuit of a transformative social protection system that can adequately tackle economic inequalities. This paper argues that a human rights approach can provide a normative orientation in the political process that decides the distribution of burdens and benefits in relation to social protection, calling for an assessment of its impact on socioeconomic inequalities and on disadvantaged groups of people. While the right to social security is at the center of a human rights approach to social protection, the rights to health, education, housing, and work also provide important normative elements for social protection. A human rights-based social protection system requires comprehensive protection for major social risks and challenges throughout the life cycle; universal access to quality services such as health, education, child care, and services for older people or people with disabilities; and a progressive financing mechanism. In this regard, the International Labour Organization's Social Protection Floors Recommendation No. 202 provides strong guidance on the implementation of the right to social security for all.